Speaking Anxiety among Learners in an International School: Types, Factors, and Coping Strategies - Amelia, Rifda (Journey: Journal of English Language and Pedagogy, 2026)
This study aims to discover the types, factors, and coping strategies of speaking anxiety among 7th-grade students in an international school. The participants comprised all 7th-graders from six classes at an international Islamic boarding school in East Java. Using a sequential explanatory mixed-methods design, questionnaires were distributed to all students to map their anxiety types, followed by semi-structured interviews with six purposively selected participants to delve deeper into the factors and coping strategies. The findings revealed that communication apprehension and fear of negative evaluation were the dominant types of speaking anxiety experienced by students, while test anxiety occurred less frequently. Several factors contribute to this speaking anxiety, including psychological, linguistic, pedagogical, and socio-cultural factors such as intensive English use demands in an international school environment. To overcome anxiety, students applied coping strategies, with preparation and peer-seeking as the most frequent strategies, followed by relaxation and positive thinking. Some students also exhibited signs of resignation. This study concludes that speaking anxiety is a complex phenomenon influenced by both internal and external factors, offering pedagogical insights for teachers and school administrators to design less-anxious speaking environments.